Participation of Gαi-Adenylate Cyclase and ERK1/2 in Mas Receptor Signaling Pathways - Burghi, Valeria; Echeverría, Emiliana B.; Sosa, Máximo H.; Quiroga, Diego T.; Muñoz, Marina C.; Davio, Carlos; Monczor, Federico; Fernández, Natalia C.; Dominici, Fernando P. (Frontiers in Pharmacology, 2019)
The MasR receptor (MasR) is an orphan G protein-coupled receptor proposed as a candidate for mediating the angiotensin (Ang)-converting enzyme 2-Ang-(1-7) protective axis of renin-angiotensin system. This receptor has been suggested to participate in several physiological processes including cardio- and reno-protection and regulation of the central nervous system function. Although the knowledge of the signaling mechanisms associated with MasR is essential for therapeutic purposes, these are still poorly understood. Accordingly, in the current study we aimed to characterize the signaling pathways triggered by the MasR. To that end, we measured cAMP and Ca2+ levels in both naive and MasR transfected cells in basal conditions and upon incubation with putative MasR ligands. Besides, we evaluated activation of ERK1/2 by Ang-(1-7) in MasR transfected cells. Results indicated the existence of a high degree of MasR constitutive activity towards cAMP modulation. This effect was not mediated by the PDZ-binding motif of the MasR but by receptor coupling to Gαi-adenylyl cyclase signaling pathway. Incubation of MasR transfected cells with Ang-(1-7) or the synthetic ligand AVE 0991 amplified MasR negative modulation of cAMP levels. On the other hand, we provided evidence for lack of MasR-associated modulation of Ca2+ levels by Ang-(1-7). Finally, it was determined that the MasR attenuated Ang-(1-7)-induced ERK1/2 phosphorylation mediated by AT1R. We provided further characterization of MasR signaling mechanisms regarding its constitutive activity and response to putative ligands. This information could prove useful to better describe MasR physiological role and development of therapeutic agents that could modulate its action.